Save me - Scottoline, Lisa (St. Martin's Press, 2011)
When an explosion rips through the nearly empty cafeteria of a Reesburgh (Pa.) Elementary School, lunch mother Rose McKenna leads two girls to safety before racing to rescue her own daughter, Melly. But Rose soon learns that she may face both civil and criminal charges for her heroics because one of the girls she saved was seriously injured in the resulting fire that killed three school staff members.